Whole crop optimization provides a viable pathway for sustainable intensification of barley-livestock farming systems - Wamatu, Jane; Ekule, Muluken; Hailemichael, Shewangizaw (International Center for Agricultural Research in the Dry Areas, 2022)
A report of a participatory varietal evaluation by farmers for food-feed traits of barley in North Shewa, Ethiopia.